A Scientometric Mapping of Global Research Productivity and Network Analysis in Animal Husbandry and Veterinary Science (Indian Journal of Animal Production and Management, 2026)
This study examines the discipline of veterinary science including animal husbandry and veterinary medicine by investigating the research articles, conference proceedings, and book chapters published in Scopus in 2006-25. The data had been obtained based on 4609 publications searched on the Scopus database. The primary conclusions made are that there is a steady growth of animal husbandry and veterinary medicine research, and the value of this area is growing. There are a variety of researchers who are playing a prominent role in animal husbandry and veterinary medicine research. According to co-authorship analysis, there has been high collaboration throughout the world, with the major contributions of such researchers as Lee, J., Wang, Y., and Wang, J., and the most prominent research centers in USA, UK, and China. Thematically significant issues like cattle, animal welfare, and risk factors were found through the use of keywords as co-occurring keywords. The changing clusters in animal keeping and veterinary science are an indication of new fields that need to be investigated. Future research must center on machine learning and advances in technology and their effects on the animal husbandry and veterinary sector, and establish new methods to deal with the growing challenges in the various environments
Keywords: Animal Husbandry, Publication Growth, Veterinary, Scientometrics, Network Analysis, Authorship Pattern